2021
DOI: 10.1051/0004-6361/202140344
|View full text |Cite
|
Sign up to set email alerts
|

IRIS observations of chromospheric heating by acoustic waves in solar quiet and active regions

Abstract: Aims. To study the heating of solar chromospheric magnetic and nonmagnetic regions by acoustic and magnetoacoustic waves, the deposited acoustic-energy flux derived from observations of strong chromospheric lines is compared with the total integrated radiative losses. Methods. A set of 23 quiet-Sun and weak-plage regions were observed in the Mg II k and h lines with the Interface Region Imaging Spectrograph (IRIS). The deposited acoustic-energy flux was derived from Doppler velocities observed at two different… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(48 reference statements)
1
8
0
Order By: Relevance
“…Therefore, the energy flux available at a height of 800 km (i.e., ∼10 4 W m −2 ) is just sufficient to balance the estimated radiative losses in the layers above this height, as estimated by Withbroe & Noyes (1977). This is in contrast to previous studies where acoustic flux was found to be insufficient to compensate for the radiative losses (Fossum & Carlsson 2005b;Beck et al 2009;Abbasvand et al 2020Abbasvand et al , 2021. Additionally, the acoustic wave flux in the height range of 250-600 km is much larger than estimated in previous studies pertaining to quiet Sun regions (Wunnenberg et al 2002;Straus et al 2008;Bello González et al 2009).…”
Section: Resultsmentioning
confidence: 72%
“…Therefore, the energy flux available at a height of 800 km (i.e., ∼10 4 W m −2 ) is just sufficient to balance the estimated radiative losses in the layers above this height, as estimated by Withbroe & Noyes (1977). This is in contrast to previous studies where acoustic flux was found to be insufficient to compensate for the radiative losses (Fossum & Carlsson 2005b;Beck et al 2009;Abbasvand et al 2020Abbasvand et al , 2021. Additionally, the acoustic wave flux in the height range of 250-600 km is much larger than estimated in previous studies pertaining to quiet Sun regions (Wunnenberg et al 2002;Straus et al 2008;Bello González et al 2009).…”
Section: Resultsmentioning
confidence: 72%
“…The temperature in the quiet chromosphere oscillates between an atmosphere in radiative equilibrium and one with a moderate chromospheric temperature rise, and horizontal canopy structure reflects itself in temperature maps at heights in the low chromosphere (Beck et al 2013). Using Ca II 853.2 IBIS data, Abbasvand et al(2020a) found that the deposited magnetoacoustic wave energy balances 30-50% radiative losses in the quiet chromosphere and 50-60% of the losses in a plage with vertical field, rising up to 70-90% in the plage regions with inclined field. This way, significant portions of the radiative losses could be compensated via acoustic wave flux which has been previously converted to magnetoacoustic wave flux in the regions with the inclined fields.…”
Section: Wave Heating Of the Large-scale Chromospherementioning
confidence: 99%
“…Magnetic reconnection and heating due to waves are not independent mechanisms, however, since magnetic reconnection can be a source of waves (Verwichte et al 2004;Jess et al 2008;Luna et al 2008;Li & Zhang 2012;Provornikova et al 2018), and waves can produce instabilities needed to trigger reconnection processes (Isobe & Tripathi 2006;Lee et al 2014;McLaughlin et al 2009). Moreover, recent advances in observational instrumentation and simulation capabilities imply that wave-based heating could be a viable process for maintaining the high temperatures of the solar atmosphere (Abbasvand et al 2020(Abbasvand et al , 2021Yadav et al 2021b). These new results have drawn renewed interest in wave-heating mechanisms, both observationally and theoretically.…”
Section: Introductionmentioning
confidence: 99%